2020
DOI: 10.3390/su12145734
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of Water Flow Glazing: Transient Response in Real Test Rooms

Abstract: The extensive use of glass in modern architecture has increased the heating and cooling loads in buildings. Recent studies have presented water flow glazing (WFG) envelopes as an alternative building energy management system to reduce energy consumption and improve thermal comfort in buildings. Currently, commercial software for thermal simulation does not include WFG as a façade material. This article aims to validate a new building simulation tool developed by the authors. Simulation results were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In addition to an accurate simulation tool, the actual challenge was to develop a monitoring system to reveal characteristic patterns of users, and to finally discover relevant design criteria that might be applicable to different orientations throughout the year. The monitoring system applied in this case study has been tested in other facilities over the last few years, and results were shown in previous articles [37,38].…”
Section: Introductionmentioning
confidence: 88%
“…In addition to an accurate simulation tool, the actual challenge was to develop a monitoring system to reveal characteristic patterns of users, and to finally discover relevant design criteria that might be applicable to different orientations throughout the year. The monitoring system applied in this case study has been tested in other facilities over the last few years, and results were shown in previous articles [37,38].…”
Section: Introductionmentioning
confidence: 88%
“…All the translucent WFG panels were connected to the same circulating device (CD TP), and the flow rate wasṁ = 1 L/min m 2 . The influence of the mass flow rate on the ability to deliver or absorb heat and the recommended values have been studied in previous articles [37]. Transparent WFG panels are exposed to solar radiation, so the mass flow rate had to be higher to absorb heat in summer and keep the water temperature within acceptable values.…”
Section: Description Of the Facilitymentioning
confidence: 99%
“…It is a second-class pyranometer according to ISO 9060 standards and the World Meteorological Organization (WMO); it had to be placed outdoors because obstacles and reflections can affect the measurements. The same monitoring equipment has been described in other articles [37]. Figure 4 shows the position of the temperature sensors in the WFG and the circulating device.…”
Section: Description Of the Sensorsmentioning
confidence: 99%